Cryogenic free-form extrusion bioprinting of decellularized small intestinal submucosa for potential applications in skin tissue engineering. (31st May 2019) - Shi, Lei; Hu, Yiqiang; Ullah, Muhammad Wajid; ullah, Ismat; Ou, Hao; Zhang, Wancheng; Xiong, Liming; Zhang, Xianglin
Abstract: A novel strategy of cryogenic 3D bioprinting assisted by free-from extrusion printing has been developed and applied to printing of a decellularized small intestinal submucosa (dSIS) slurry. The rheological properties, including kinetic viscosity, storage modulus (G′), and loss modulus (G″), were appropriate for free-from extrusion printing of dSIS slurry. Three different groups of scaffolds, including P500, P600, and P700, with filament distances of 500, 600, and 700 μ m, respectively were fabricated at a 5 mm s −1 working velocity of the platform ( V xy ) and 25 kPa air pressure of the dispensing system ( P ) at −20 °C. The fabricated scaffolds were crosslinked via 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) which resulted in a polyporous microstructure. The variations in the filament diameter and pore size were evaluated in the initial frozen state after printing, the lyophilized state, and after immersion in a PBS solution. The Young's modulus of the P500, P600, and P700 scaffolds was measured in wet and dry states for EDC-crosslinked scaffolds. The cell experiment results showed improved cell adhesion, viability, and proliferation both on the surface and within the scaffold, indicating the biocompatibility and suitability of the scaffold for 3D cell models. Further, gene and protein expression of normal skin fibroblasts on dSIS scaffolds demonstrated their ability to promote the production of some extracellular matrix proteins (i.e. collagen I, collagen III, and fibronectin) in vitro . Overall, this study presents a new potential strategy, by combining cryogenic 3D bioprinting with decellularized extracellular matrix materials, to manufacture ideal scaffolds for skin tissue engineering applications.